Perception of women entrepreneurship in ancient Greek and traditional Yoruba societies (2021)
Globally, economic growth and national development may be the result of the success registered by Small and Medium-Scale Enterprises (SMEs). In the societies or nations where the intervention by SMEs is a thriving practice, credit often is given mainly to the male entrepreneurs while the contributions of their female counterparts hardly receives much robust consideration in existing literature. Thus, this paper takes a diachronic approach in explicating the perceptions and contributions of women. The study is delimited to the antiquated Grecian society and the Yoruba society of Nigeria in the pre-colonial and colonial periods and adopts a comparative hermeneutical approach in the analysis of the historical findings and textual materials peculiar to both societies. Its findings reveal that significant dichotomies existed in both societies in relation to the entrepreneurial activities of women. In Greece, women were inhibited by their cultural value to engage in entrepreneurship. The entrepreneurial activities they were allowed to carry out were more passive than active. Nonetheless, they excelled and provided stability at the home front and the nation Overall albeit on a micro-managed scale. On the other hand, Yoruba women in Nigeria were privileged to engage in entrepreneurial activities with minimal restrictions. This afforded them the opportunity to translate their business enterprises into money spinning ventures. With such wealth in their hands, they could conveniently delve into politics and have a telling influence in the political affairs of their various communities. The study therefore underscores the historicity that women in different societies have found a way to counter patriarchy through diligence, dexterity, creativity and innovation to ensure domestic stability and sustainable development in every society. Thus, women should not be perceived as belonging strictly to the 'other room’. Such perception is tantamount to a subtle denial of their pivotal contributions to economic development and socio-political advancement whether in the past or present times